(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2017)
This study deals with the main lexical features of Omani dialect, the study highlights the impact of terms consistency on the function of Omani dialect as a communication means, and it examines the consistency influence on the status of originality and modernity of the Omani community dialect, and the capacity of its members to keep abreast with developments in all their aspects of life over times. To achieve its purposes, the study adapted descriptive method and selected terms from Omani dialect that reflect the effect of consistency and change, and signify life developments in Oman. The study reveals, among its other results, that multiple sources shape the lexical corpus of Omani dialect, and the derived and conventionalized terms used by Omanis are the most fixed. Furthermore, usage can be considered as a vital rule in linguistic development, as significance change is bound to the term usage.